The Impact of Blood Flow Restriction Training on Tibial Bone Stress Injury Rehabilitation: An Exploratory Case Series - Andrew P Golden; Kathleen K Hogan; Jamie B Morris; Bryan B Pickens (North American Sports Medicine Institute, 2024)
# Background Lower extremity bone stress injuries (BSI) are common injuries among athletes and military members. Typical management involves a period of restricted weightbearing which can have rapid detrimental effects upon both muscle and bone physiology. Few studies have investigated the effect of blood flow restriction (BFR) training on bone in the rehabilitative setting. # Purpose The purpose of this study was to investigate the effects of lower extremity exercise with the addition of BFR upon bone mineral density, bone mineral content, and lean body mass in military members with tibial BSIs. # Study Design Case series # Methods Twenty military members with MRI-confirmed tibial BSI were recruited to complete lower extremity exercise with the addition of BFR twice per week for four weeks. The BFR cuff was applied proximally to the participant's involved limb while they performed gluteal, thigh, and leg resistance exercises. Outcomes were assessed at baseline and four weeks. The primary outcomes were whole leg bone mineral density (BMD), bone mineral content (BMC), and lean body mass (LM) as measured by dual-energy x-ray absorptiometry. Secondary outcomes included thigh and leg circumference measures and patient-reported outcomes, including the Lower Extremity Functional Scale (LEFS), Patient-Reported Outcomes Measurement Information System 57 (PROMIS-57), and Global Rating of Change (GROC). # Results No significant differences were found in BMD (p=0.720) or BMC (p=0.749) between limbs or within limbs over time. LM was generally less in the involved limb (p=0.019), however there were no significant differences between or within limbs over time (p=0.404). For thigh circumference, significant main effects were found for time (p=0.012) and limb (p=0.015), however there was no significant interaction effect (p=0.510). No significant differences were found for leg circumference (p=0.738). Participants showed significant mean changes in LEFS (15.15 points), PROMIS physical function (8.98 points), PROMIS social participation (7.60 points), PROMIS anxiety (3.26 points), and PROMIS pain interference (8.39 points) at four weeks. # Conclusion The utilization of BFR in the early rehabilitative management of tibial BSI may help mitigate decrements in both bone and muscle tissue during periods of decreased physical loading. # Level of Evidence 4